(3GOGAgG GdeGdj h GKQgG aj Shb GdChQGb GdeGdjIs - (3MjOQ jhfS(B, (3GdehShjs ((3YeGf(B:s (3OGQ GdjGRhQj ddfTQ hGdJhRjY(B,s, 2011)
(3fTCI GdeUGQa GdGSdGejI h CSSgG GdfXQjI , GdHfGA Gdgjcdj ddCShGb GdeGdjI, GdeUGQa GdGSdGejI h GdJMOjGJ GdYGdejI GdLOjOI , fTCI h JWhQ GdfTGW GdeUQaj GdGSdGej aj cd ef GdCQOf h GdSYhOjI , JMdjd COGA Shbj GdChQGb GdeGdjI aj GdCQOf h GdSYhOjI ddeOI (B1990 (3`` (B2007 (3bjGS h JMdjd CKQ GdCOGA GdeGdj ddeUGQa GdGSdGejI Ydi eDTQGJ Shb GdChQGb GdeGdjI aj GdCQOf h GdSYhOjI (B.s
(3agGQS U(B.10 (3eQGLY U(B.263 (3; edGMb U(B. 253(3LOGhd U(B.10(3; GTcGd U(B.13((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdCShGb GdeGdjIs; (3GdGhQGb GdfbOjIs; (3GdHfhc GdGSdGejs